OP0284 Long Noncoding RNA MIR503HG is a Novel Factor in the Pathogenesis of Systemic Sclerosis. (9th June 2015) - Pachera, E.; Assassi, S.; Salazar Cintora, G.; Frank-Bertoncelj, M.; Haunerdinger, V.; Dobrota, R.; Brock, M.; Vettori, S.; Hellerbrand, C.; Feghali-Bostwick, C.; Distler, J.; Kania, G.; et al.
Abstract : Background: Long noncoding RNAs (LncRNAs) are a novel class of noncoding transcripts with diverse regulatory functions, e.g. imprinting regulation, dosage compensation, cell cycle regulation, pluripotency and retrotransposon silencing. Dysregulation of lncRNAs is increasingly recognized to contribute to the disease pathogenesis, such as cancer, autoimmune disorders and neurodegeneration. Objectives: To identify candidate lncRNAs in systemic sclerosis (SSc) and investigate their function, in particular in relation to the TGFβ pathway and myofibroblast phenotype development. Methods: RNA Sequencing Ilumina HiSeq2000 was performed in healthy and SSc skin biopsies. Human skin fibroblasts were isolated from biopsies of SSc patients and healthy controls (HC), human pulmonary smooth muscle cells were purchased from Lonza. The cells were treated with 10 ng/ml TGFβ. TGFβR1 inhibitors (SD208 and SB431542) and siRNA against SMAD3 were used to investigate TGFβ driven gene expression. The lncRNA MIR503HG was silenced in skin fibroblasts using locked nucleic acid antisense oligonucleotides (LNA GapmeRs), followed by qPCR analyses and immunofluorescence staining. The expression of MIR503HG was measured in tissue samples of liver and lung fibrosis. Results: RNA sequencing showed a significant upregulation of the lncRNA MIR503HG (H19X) in SSc versus HC skin biopsies. Importantly, the upregulation of MIR503HG was not limited to SSc skin, but present also in the tissues from liver and lung fibrosis, indicating a broader role of MIR503HG in fibrotic diseases. While there was no difference in the basal expression of MIR503HG between SSc and HC cultured dermal fibroblasts, MIR503HG was strongly and consistently induced by TGFβ. Induction of MIR503HG by TGFβ was not limited to skin fibroblasts, but evident also in other cell types relevant for SSc, e.g. pulmonary vascular smooth muscle cells. Time curve analysis revealed that the upregulation of MIR503HG by TGFβ was strongest after 6h reaching 12.8±0.7 induction; and dose curve analysis showed a steady increase of MIR503HG over physiologically relevant TGFβ concentrations. These effects were TGFβR1 dependent as shown by the inhibition experiments with the chemical inhibitors SD208 and SB431542. Moreover, the upregulation of MIR503HG by TGFβ was significantly impaired by silencing of SMAD3, further pointing to an important role of the canonical TGFβ pathway in MIR503HG expression. The knockdown of MIR503HG in skin fibroblasts led to a strong down regulation of COL1A1, fibronectin and αSMA mRNAs, indicating a potential involvement of MIR503HG in the development of a myofibroblast phenotype. Additionally, immunofluorescence staining showed reduced αSMA formation in MIR503HG silenced skin fibroblasts. Conclusions: This is the first study reporting changes in long-non coding RNAs in SSc and across fibrotic organs. It opens new perspectives in the pathogenesis of fibrotic diseases by this novel class of regulatory, non-coding RNAs. Disclosure of Interest: E. Pachera: None declared, S. Assassi: None declared, G. Salazar Cintora: None declared, M. Frank-Bertoncelj: None declared, V. Haunerdinger: None declared, R. Dobrota Grant/research support from: Pfizer, Actelion, M. Brock: None declared, S. Vettori Grant/research support from: Pfizer, Roche, Consultant for: Phadia-Thermofischer, Speakers bureau: Pfizer, Abbvie, C. Hellerbrand: None declared, C. Feghali-Bostwick: None declared, J. Distler: None declared, G. Kania: None declared, O. Distler Grant/research support from: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation, Consultant for: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation